PENINGKATAN KUALITAS PEMBELAJARAN SANGGAR SENI TARI ANAK BERKEBUTUHAN KHUSUS - Yuliastuti, Ida Ayu Nyoman; Artajaya, I Wayan Eka; Susrawan, I Nyoman Adi (Universitas Esa Unggul, 2018)
AbstractSekar Dewata dance studio and Jari Menari dance studio still experience problems in improving the quality of learning for children with special needs. The lack of visual facilities that are owned and the lack of teaching standards between one teacher and another teacher makes the learning process less attractive and difficult to understand by children with special needs. In overcoming these problems, the implementation method used is the procurement of equipment, counseling, training, mentoring and coaching. The equipment provided in this service is a sound system, LCD projector, and mirror glass replacement. In addition to procurement of equipment, counseling is also conducted on how to use these tools. This is useful to support the learning systems of the two dance studios to be more effective and can be easily understood by children with special needs. Other activities that have been carried out are training and mentoring in the preparation of standard operating procedures. This is useful to help dance studios have standards in teaching, so that there is a suitability of the teaching system between dance instructors and other dance instructors. With this dedication activity, the quality of learning in both partners has increased and children with special needs are quicker to understand each dance movement taught. The service activities that have been carried out are expected to encourage children with special needs to be more enthusiastic and more confident in participating in dance performances so that they can show their talents and potential.Ã‚Â Keywords: children with special needs, dance art studio, standard operating proceduresÃ‚Â AbstrakSanggar tari Sekar Dewata dan sanggar tari Jari Menari masih mengalami kendala dalam meningkatkan kualitas pembelajaran untuk anak berkebutuhan khusus. Kurangnya sarana visual yang dimiliki dan belum adanya standar pengajaran antara pengajar satu dengan pengajar lainnya membuat proses pembelajaran menjadi kurang menarik dan susah untuk dimengerti oleh anak berkebutuhan khusus. Dalam mengatasi permasalahan tersebut, metode pelaksanaan yang digunakan yaitu pengadaan peralatan, penyuluhan, pelatihan, pendampingan dan pembinaan. Peralatan yang diberikan dalam pengabdian ini adalah sound system, lcd projector, dan penggantian kaca cermin. Selain pengadaan peralatan juga dilakukan penyuluhan cara penggunaan alat-alat tersebut. Hal ini berguna untuk menunjang sistem pembelajaran kedua sanggar tari agar lebih efektif dan dapat mudah dimengerti oleh anak berkebutuhan khusus Kegiatan lainnya yang telah dilakukan yaitu pelatihan dan pendampingan dalam pembuatan standar operasional prosedur. Hal ini berguna untuk membantu sanggar tari memiliki standar dalam pengajaran, sehingga terjadi kesesuaian sistem pengajaran antara pengajar tari satu dengan pengajar tari lainnya. Dengan adanya kegiatan pengabdian ini, kualitas pembelajaran pada kedua mitra mengalami peningkatan dan anak berkebutuhan khusus lebih cepat memahami setiap gerak tari yang diajarkan. Kegiatan pengabdian yang telah dilaksanakan ini, diharapkan dapat mendorong anak berkebutuhan khusus agar lebih bersemangat dan lebih percaya diri dalam mengikuti kegiatan pagelaran seni tari, sehingga dapat menunjukkan bakat dan potensi yang dimiliki.Ã‚Â Kata kunci: anak berkebutuhan khusus, sanggar seni tari, standar operasional prosedur